2022
DOI: 10.3390/su141711015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Nutritional Value of Selected Wild Food Plants in Türkiye and Their Promotion for Improved Nutrition

Abstract: Türkiye represents one of the world’s biodiversity hotspots, containing over 11,000 species of plants, with an estimated 10% being edible. Wild food plants, especially in rural areas, are collected and eaten or sold in local markets, complementing people’s diets, and represent a source of additional income for foraging households. Yet, the use of wild food plants is declining, with both their dietary and cultural values being undermined. Wild food plants can be used as a healthy dietary alternative to imported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…We can interpret these results obtained with different dimensions as being related to our macro-level comparison analysis. In their study, Borelli et al ( 48 ) mentioned that Turkey’s risk of food insecurity, which is also influenced by housing, has been increasing in recent years. In a 2017 study in Turkey, Ipek ( 49 ) found that an increase in income level, education level, and healthcare expenditures significantly reduced food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…We can interpret these results obtained with different dimensions as being related to our macro-level comparison analysis. In their study, Borelli et al ( 48 ) mentioned that Turkey’s risk of food insecurity, which is also influenced by housing, has been increasing in recent years. In a 2017 study in Turkey, Ipek ( 49 ) found that an increase in income level, education level, and healthcare expenditures significantly reduced food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the speci c context of Sundanese communities, lalap encompasses both wild/non-cultivated and semi-domesticated edible plants. Numerous studies underscore the high nutritional value of wild edible plants [9,35,[37][38][39], as evidenced by different documented groups of WUNEPs (Table 1). The nutritional composition of the selected WUNEPs is examined, along with their potential contribution to the RDA of certain nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional signi cance of the documented WUNEPs is apparent, as many of them provide essential nutrients and have a higher nutritional value compared to common vegetables [35,37,127]. Therefore, promoting the inclusion of these plants in diets could improve the nutritional status of not only indigenous and rural populations [13,128,129] but also the rest of the population [5].…”
Section: Mineral and Vitamin Contentmentioning
confidence: 99%
“…Previous Indonesian studies also revealed that Sundanese communities residing in the Eastern Priangan areas and indigenous communities of Mentawai still highly value and prefer their traditional foods, thus sustaining the use of WEPs [22,24]. The potential nutritional and dietary contribution of documented WEPs Numerous studies underscore the high nutritional value of wild plants [8, 43,47,62,74], as evidenced by different documented groups of WEPs (Table 1). Their potential contribution to the RDA demonstrates that some of them can serve as a 'source' (RDA > 15%) or contain 'high level' (RDA > 30%) of certain nutrients (Table 3).…”
Section: Wep Consumption: Perceptions and Associated Factorsmentioning
confidence: 99%